The Relative Income and Relative Deprivation Hypotheses : A Review of the Empirical Literature - Verme, Paolo (World Bank, Washington, DC, 2013)
The paper provides a review of the empirical literature in economics that has attempted to test the relative income hypothesis as put forward by Duesemberry (1949) and the relative deprivation hypothesis as formalized by Runciman (1966). It is argued that these two hypotheses and the empirical models used to test them are essentially similar and make use of the same relative income concept. The review covers the main intellectual contributions that led to the formulation and tests of these hypotheses, the main formulations of the utility and econometric equations used in empirical studies, the main econometric issues that complicate tests of the hypotheses, and the empirical results found in the literature. The majority of studies uses absolute and relative income together as explanatory factors in utility models and finds absolute income to have a positive and significant effect on utility (happiness). The majority of studies also finds relative income to be a significant factor in explaining utility but the sign of this relation varies across studies. The source of this variation is complex to detect given that few results are directly comparable across studies because of differences in model specifications.